2012
DOI: 10.2105/ajph.2011.300425
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Iraq/Afghanistan Deployments on Major Depression and Substance Use Disorder: Analysis of Active Duty Personnel in the US Military

Abstract: Objectives. Our objective was to analyze the association between deployment characteristics and diagnostic rates for major depression and substance use disorder among active duty personnel. Methods. Using active duty personnel serving between 2001 and 2006 (n = 678 382) and deployment information from the Contingent Tracking System, we identified individuals diagnosed with substance use disorders and major depression from TRICARE health records. We performed logistic regression analysis to assess the effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(59 citation statements)
references
References 18 publications
1
58
0
Order By: Relevance
“…All else being equal, a longer deployment increases the probability that a given service member will be exposed to a traumatic experience on that deployment, which puts him or her at increased risk for psychological and behavioral health problems. Thus, although there has been some evidence to suggest that longer deployments have a bivariate association with PTSD Allison-Aipa et al, 2010;Armed Forces Health Surveillance Center, 2012;Escolas et al, 2013;Macera et al, 2013;MacGregor et al, 2013;Shen, Arkes, and Williams, 2012), depression Allison-Aipa et al, 2010;Shen, Arkes, and Williams, 2012), and substance misuse (Allison-Aipa et al, 2010;Mustillo et al, 2015;Rona et al, 2007;Shen, Arkes, and Williams, 2012;Spera et al, 2011;Wittchen et al, 2013), only two of the studies that showed an association between deployment length and behavioral health outcomes controlled for combat-related traumatic events (Mustillo et al, 2015;Spera et al, 2011). In contrast, several studies that do adjust for combat exposure find no evidence of an association between deployment length and PTSD, depression, and substance misuse (Gehrman et al, 2013;Grieger et al, 2006;Mustillo et al, 2015;Schultz, Glickman, and Eisen, 2014;Seelig et al, 2012;Wood et al, 2012).…”
Section: Deployments and Psychological And Behavioral Healthmentioning
confidence: 99%
“…All else being equal, a longer deployment increases the probability that a given service member will be exposed to a traumatic experience on that deployment, which puts him or her at increased risk for psychological and behavioral health problems. Thus, although there has been some evidence to suggest that longer deployments have a bivariate association with PTSD Allison-Aipa et al, 2010;Armed Forces Health Surveillance Center, 2012;Escolas et al, 2013;Macera et al, 2013;MacGregor et al, 2013;Shen, Arkes, and Williams, 2012), depression Allison-Aipa et al, 2010;Shen, Arkes, and Williams, 2012), and substance misuse (Allison-Aipa et al, 2010;Mustillo et al, 2015;Rona et al, 2007;Shen, Arkes, and Williams, 2012;Spera et al, 2011;Wittchen et al, 2013), only two of the studies that showed an association between deployment length and behavioral health outcomes controlled for combat-related traumatic events (Mustillo et al, 2015;Spera et al, 2011). In contrast, several studies that do adjust for combat exposure find no evidence of an association between deployment length and PTSD, depression, and substance misuse (Gehrman et al, 2013;Grieger et al, 2006;Mustillo et al, 2015;Schultz, Glickman, and Eisen, 2014;Seelig et al, 2012;Wood et al, 2012).…”
Section: Deployments and Psychological And Behavioral Healthmentioning
confidence: 99%
“…Many studies use convenience samples, without a control group, and compare mental health rates before and after an OEF/OIF mission. The studies that compared military personnel who deployed with those who did not deploy generally find that the risk of PTSD and other mental health problems increased substantially after a service member returned from an OEF/OIF mission (Shen et al 2010;Shen, Arkes, and Williams 2012;Cesur, Sabia, and Tekin 2013). Similarly, suicide deaths have been found to be higher upon return from an OEF/OIF mission (Shen, Cunha, and Williams 2016).…”
Section: Background On Military Deployments and Mental Healthmentioning
confidence: 99%
“…A large literature has documented the increased incidence of mental health problems among deployed service members (see, for example, Hoge et al, 2006;Tanielian and Jaycox 2008;Shen, Arkes, and Williams 2012;Cesur, Sabia, and Tekin 2013;Shen, Cunha, and Williams 2016). It is difficult to isolate the cause of these mental health problems, but likely candidates include both the acts of killing and trying not to be killed, as well as other associated horrors of war.…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted by Shen et al looked at a series of population-based studies of the U.S. Military between 2001 and 2006 and found that the "incidence of a newly diagnosed substance abuse disorder ranged from 6% to nearly 9%, overall." When looking at the Marine Corps in particular, this number nearly doubles from 5% to 9.3% when the sample is reduced to only Marines who have deployed in support of OIF or OEF (Shen, Arkes, & Williams, 2012). This is significant because the data used for this thesis looks at Marines serving between 2001 and 2011, when the percentage of active duty combat veterans was at its highest.…”
Section: Substance Abusementioning
confidence: 99%